2014
DOI: 10.1007/s13197-014-1316-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of leaves (drumstick, mint and curry leaves) powder as natural preservatives in restructured chicken block

Abstract: The use of natural preservatives to increase the shelf-life of meat products is promising as they possess antioxidant and antimicrobial properties. Earlier, a highly acceptable restructured chicken slice without the addition of extra fat was developed in the same laboratory which was acceptable up to 10th day of storage under refrigeration and spoilage was mainly due to oxidation. Hence, the present study was planned to determine the efficacy of certain plant leaves' (drumstick, mint and curry leaves) powder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 10 publications
(12 reference statements)
3
18
0
Order By: Relevance
“…Similar decline in colour and appearance score during storage have been reported by Zargar et al, (2014) in a chicken sausages; Najeeb et al, (2014) in restructured chicken slices and Giriprasad et al, (2015) in restructured buffalo meat steaks.…”
Section: Sensory Evaluation Of Goat Meat Patties Colour and Appearancsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar decline in colour and appearance score during storage have been reported by Zargar et al, (2014) in a chicken sausages; Najeeb et al, (2014) in restructured chicken slices and Giriprasad et al, (2015) in restructured buffalo meat steaks.…”
Section: Sensory Evaluation Of Goat Meat Patties Colour and Appearancsupporting
confidence: 81%
“…Tarladgis et al, (1960) described that TBARS values were highly correlated with sensory scores of trained panellist. Similar declining in flavour score during storage reported by Thomas et al, (2006) in buffalo meat nuggets; Zargar et al, (2014) in a chicken sausages; Najeeb et al, (2014) in restructured chicken slices and Giriprasad et al, (2015) in restructured buffalo meat steaks. Similar result was found by Gomez and Lorenzo (2012) in foal steaks which were packed under various conditions.…”
Section: Flavour Scores Of Meat Pattiessupporting
confidence: 71%
“…In addition, Hawashin, Al-Juhaimi, Mohamed Ahmed, Ghafoor, and Babiker (2016) reported that the moisture content of raw beef patties gradually decreased as the concentration of defatted olive cake increase, whereas the protein and fat showed a gradual increase. Moreover, Najeeb et al (2015) reported that incorporation of the moringa leaf powders at 1% level did not show any significant differences in moisture, protein, fat, and ash of the restructured chicken slices compared to both control and reference products during storage. Furthermore, Baldin et al (2016) indicated that addition of microencapsulated jabuticaba (Myrciaria cauliflora) extract to fresh sausages insignificantly affected the moisture, fat, protein, and ash contents of the product.…”
Section: Effect Of Mlp On Chemical Composition Of Chicken Pattiesmentioning
confidence: 96%
“…Thus, these constituents might be responsible for low total plate count in MLP-containing chicken patties. Similarly, incorporation of moringa leaf extracts was reported to reduce the total plate count during the storage of various meat products (Falowo et al, 2016;Najeeb et al, 2015;Shah et al, 2015). In addition, Jayawardana et al (2015) reported that the total plate count of chicken sausages formulated with 0.5%, 0.75%, and 1% moringa leaves was significantly lower than that of the control during the storage period.…”
Section: Effect Of Mlp On Microbial Load Of Chicken Pattymentioning
confidence: 98%
See 1 more Smart Citation